1998
DOI: 10.1002/chin.199837253
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis, in vitro anti‐HIV Activity, and Biological Stability of 5′‐O‐Myristoyl Analogue Derivatives of 3′‐Fluoro‐2′,3′‐dideoxythymidine (FLT) as Potential Bifunctional Prodrugs of FLT.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…5′- O -(Fatty acyl) esters of FTC ( 5 – 7 ) were consistently active against both cell-free and cell-associated virus, and exhibited higher anti-HIV activity than FTC (Table ). The FTC esters displayed the highest anti-HIV activity against cell-free virus (EC 50 = 0.04–0.2 μM) among all the previously reported fatty acyl ester derivatives and their parent NRTIs. , …”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…5′- O -(Fatty acyl) esters of FTC ( 5 – 7 ) were consistently active against both cell-free and cell-associated virus, and exhibited higher anti-HIV activity than FTC (Table ). The FTC esters displayed the highest anti-HIV activity against cell-free virus (EC 50 = 0.04–0.2 μM) among all the previously reported fatty acyl ester derivatives and their parent NRTIs. , …”
Section: Resultsmentioning
confidence: 88%
“…The polar nature of FTC (calculated Log P for FTC = −1.29) limits its efficient cellular uptake. We have previously reported the synthesis and evaluation of fatty acyl ester prodrugs of 3TC, AZT, d4T, and FLT. , These studies showed improvement in the anti-HIV activities of nucleoside analogues after conjugation with myristic acid analogues. ,, In addition, myristic acid analogues have moderate activity against N -myristoyltransferase (NMT), a crucial enzyme involved in the life cycle of HIV (e.g., capsid protein p17, Pr160 gag‑pol , Pr55 gag , p27 nef ). , NMT catalyzes the myristoylation of viral proteins at N -terminal glycine and makes them more hydrophobic to improve their protein–protein and protein–membrane interactions . Several myristic acid analogues inhibit NMT, thereby reducing replication of HIV-1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported the synthesis and evaluation of several 5′- O -fatty acyl esters of AZT, FLT, and 2′,3′-didehydro-2′,3′-dideoxythymidine (d4T) for inhibition of HIV-1. These conjugates were designed to achieve anti-HIV activity through inhibition of reverse transcriptase and NMT by nucleosides and fatty acids.…”
Section: Introductionmentioning
confidence: 99%